IMPACT OF E – COMMERCE ON THE STORAGE OPERATIONS OF AIR CARGO - Salim Saleh Al Shabibi , Mohammed; Ullah, Dr. Asad (IJRDO - Journal of Business Management, 2023)
Like wildfire, the e-commerce boom has spread to virtually every industry. The impact of this new digital commerce model on the air cargo sector is far-reaching and complex. By understanding how e-commerce affects the business operations of traditional air cargo companies, we can better prepare for its future development. Storage occupies a central role in any Supply Chain. The primary purpose of storage activity is to act as a buffer to adopt to the variability of the flow of production, consolidation of products and to add marginal value such as pricing, labelling or customization. Thus, in this research work the main aim of the researcher is to highlight the impact of E- commerce on Air cargo storage operations, followed by the opportunities and challenges associated with it. This study is based on the review of various literatures related to the topic of study. The study highlights that e commerce is changing the way people consume. The goal of increasing delivery speed while remaining cost effective poses significant new challenges for supply chains as they move on to satisfy the growing and fast-changing demand.